2022
DOI: 10.3390/ijms23137108
|View full text |Cite
|
Sign up to set email alerts
|

Are Alterations in DNA Methylation Related to CKD Development?

Abstract: The modifications in genomic DNA methylation are involved in the regulation of normal and pathological cellular processes. The epigenetic regulation stimulates biological plasticity as an adaptive response to variations in environmental factors. The role of epigenetic changes is vital for the development of some diseases, including atherogenesis, cancers, and chronic kidney disease (CKD). The results of studies presented in this review have suggested that altered DNA methylation can modulate the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…DNA methylation is an epigenetic mechanism involving the transfer of methyl groups to the C5 site of cytosine to form 5-methylcytosine in mammalian genomes, 10 which is related to inflammation and fibrosis. 11 DNA methylate modification is regulated by methyltransferase and demethylase. 12 DNA methyltransferase 3A (DNMT3A) is a de novo methyltransferase necessary for mammalian development.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is an epigenetic mechanism involving the transfer of methyl groups to the C5 site of cytosine to form 5-methylcytosine in mammalian genomes, 10 which is related to inflammation and fibrosis. 11 DNA methylate modification is regulated by methyltransferase and demethylase. 12 DNA methyltransferase 3A (DNMT3A) is a de novo methyltransferase necessary for mammalian development.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, renal methylation signatures also accurately reflect the presence of kidney cancer, with the methylome of RCC cells exhibiting a significantly older biological age, a phenomena seen in a wide range of cancers. Moreover, it has been shown that specific DNA methylation signatures predict various clinical outcomes, and correlate with renal function (Lu et al 2019; Dritsoula et al 2021; Rysz et al 2022; Schlosser et al 2021).…”
Section: Introductionmentioning
confidence: 99%